ANALISIS IMPLEMENTASI AKAD KAFALAH DALAM PRAKTIK BANK GARANSI SEKTOR KONSTRUKSI (STUDI KASUS KB BUKOPIN SYARIAH YOGYAKARTA) - Nurleva, Gina; Shofiyah, Indah (JURNAL ILMIAH EDUNOMIKA, 2024)
Bank guarantee is a guarantee in the form of a note issued by a bank that creates an obligation to pay the recipient of the guarantee if the guaranteed party defaults. Specifically, the purpose of this research is to investigate the implementation of the Kafalah contract in the practice of Bank Guarantee in the construction sector at Bank KB Bukopin Syariah Yogyakarta. Data collection is done through observation by seeing the actual conditions in the field, and interviews with parties related to the field of research. The method used in this research uses qualitative research. The results of the study show that in providing Bank Guarantee at KBBS Yogyakarta, customers are required to have a Bid Bond, Performance Bond, Advance Payment Bond, Maintenance Bond, and Payment Bond with a minimum guarantee deposit of 100% of the value of the Bank Guarantee. In general, the application of the concept of Kafalah in the practice of Bank Guarantee at KBBS Yogyakarta has fulfilled the elements allowed in Islamic economics because of the human need to help each other and avoid losses from debtors.